Catalogue of the Library of Philips van Marnix van Sint-Aldegonde, sold by auction (July 6th, 1599) : Facsimile of the 1599 Edition (Leiden, Gujot) - Sint-Aldegonde, Philips van Marnix van, (European History and Culture - Book Archive pre-2000., 1964)
Introduction and facsimile.